Praktik Pemberian Makan Sebagai Faktor Penyebab Stunting pada Balita: Sebuah Narrative Review - Sri Hendrawati; Rahmawati Nur Baeti (Universitas Galuh, 2025)
Stunting is Indonesia's most significant nutritional problem, with an incidence rate that tends to increase, reaching 29.6%. One of the causes of stunting is inappropriate feeding. It is influenced by social, cultural, and economic factors. This literature study purposed to identify toddlers feeding practice to the incidence factors of stunting. This literature study method is a narrative review. The framework of the narrative review process, according to Ferrari (2015), consists of five stages, namely identifying scientific literature in the database, identifying keywords, selecting articles database, identifying keywords, selecting articles, writing the results and discussion. Articles were collected from Cinahl, Pubmed, and Google Scholar. The keywords used were